The Religious Aspects of the Cossacks’ Uprisings in the First Half of 17th Century - Drozdowski, Mariusz Robert (Poznańskie Studia Slawistyczne, 2016)
This paper focuses mostly on the religious aspects of the Cossacks’ uprisings in the first half of 17th century (mainly the 1625, 1630, 1637 and 1638 uprisings), and discusses their impact on the origins, the course and following peace negotiations as well. The paper is based mostly on Cossack primary sources like manifestos, proclamations issued by the leaders, together with the directions which were to be followed during the peace talks, and the not Cossack sources as well. They prove how the religious aspects, namely the appeals to defend the persecuted orthodox confession, contributed to the character of the developments. Another question was, to what extent the religious engagement of the Cossacks uprisings at that time was caused by a sincere concern for the Orthodox Church situation, or perhaps there were other reasons, not having much in common with the faith. The analysis discusses also the Cossack delegates’ actions and policy on the Commonwealth Sejm in the years 1631–33, during which they firmly demanded restoration of the status the Orthodox Church had before 1596.